Contribuições da cromatografia circular de Pfeiffer para a análise da saúde do solo - Barros, Carlos Eduardo (2020)
Soil depletion is a process resulted from the management adopted by agriculture activity which consequently causes an ecological and social crisis. In the midst of such a context, agroecology as a movement, science and practice, values the diversification of food production while respecting the edaphoclimatic conditions of ecosystems. To apply this agriculture proposal, it is essential methods that assess the impacts on soils resulted from practices adopted in agro-ecosystems. Pfeiffer chromatography is a diagnostic tool, which is a method considerably simple and low-cost. This article aimed to understand the state of soil health in four different land-uses in a certified biodynamic site: an agroforestry system, a banana plantation with green manure, a fallow area and a forest fragment in the State of Sao Paulo, Brazil. For this, the Pfeiffer chromatography method was used and soil physical-chemical attributes were examined. The qualitative and quantitative outcomes obtained are enough to affirm that the soils of the fragment area and the agroforestry system are healthier than those of the banana area with green manure and fallow. Chromatography was a sensitive and efficient method to analyze the health of tropical soils, with the potential to be used by rural families.